INTERCULTURAL FOREIGN LANGUAGE EDUCATION IN UKRAINE IN THE CONTEXT OF THE SECONDARY SCHOOL REFORM - Nikolaeva, Sofiya (Advanced Education, 2017)
The article highlights the results of the achievements and shortcomings analysis of the secondary school reform in Ukraine, including the foreign languages teaching reform, started in 2016. The appropriate investigation methods are used. On the whole, the following techniques are applied: comparison and system analysis of methodological sources, generalisation and conceptualisation, synthesis generalisation of the positive experience of the foreign language training in secondary school, observation of the educational process and reflection, testing the school-leavers, data collection, monitoring of the Ukrainian secondary schools official sites. The article shows that in order to achieve the goals of education envisaged in the reform, it is necessary to shift from “teaching a foreign language” to “intercultural foreign language education”. Some ways of realisation of such education in the aspect of the above-mentioned reform are offered. It has been concluded that Ukraine has achieved a lot in teaching foreign languages during the independence years, but many of the key issues need solution, especially the development of the educational standards for teachers and students.